Sistem Informasi Geografis untuk Analisis Keterjangkauan Layanan Kesehatan Di Kabupaten Gorontalo - Noho, Febriyanti; Rijal, Ahmad Syamsu; Dangkua, Talha; Maulana, Karina Meiyanti; Hendra, Hendra (Universitas Negeri Makassar, 2025)
Equitable spatial access to health services is a key indicator of public service performance and territorial justice. This study analyzes the spatial distribution pattern and service catchment of government health facilities in Gorontalo Regency, Indonesia, using Geographic Information Systems (GIS). A spatially oriented descriptive-quantitative design was applied. Facility location coordinates were collected via GPS field survey and combined with secondary administrative and population data. ArcGIS 10.5 was used for two core analyses: (1) Average Nearest Neighbor to evaluate spatial distribution; and (2) buffer analysis to classify service accessibility into four distance bands (0–1,000 m; 1,001–2,000 m; 2,001–3,000 m; >3,000 m) with reference to national planning guidelines. Results show a dispersed distribution pattern (T = 1.421; p < 0.01), indicating facilities have been placed to avoid clustering. Accessibility mapping reveals that 56.89% of settlement area lies within the “moderate” (1–2 km) service band, whereas 4.99% remains beyond 3 km, suggesting residual spatial inequality. Large, sparsely settled districts such as Asparaga exhibit wide catchments served by a single primary facility, highlighting potential service strain and travel burden. Findings demonstrate the operational value of GIS for rapid spatial equity assessment in subnational health planning. The study’s novelty lies in integrating Nearest Neighbor statistics with policy-referenced distance buffers using current, field-verified facility coordinates in a rural-regency context.